Penerapan Parent-Child Interaction Therapy (PCIT) untuk Menangani Masalah Perilaku Disruptive pada Anak Usia Prasekolah - Anindya Dewi Paramita; Fawzia Aswin Hadis; Fenny Hartiani (Fakultas Psikologi Universitas Pancasila, 2019)
Disruptive behavior is a term that covers areas such as series of temper tantrums, too much crying and complaining, continually demands attention, disobey and against parents’ rules, aggressive against themselves or others, stealing, lying, destructive, and violent (Schroeder & Gordon, 2002). This study examine the effectiveness of Parent-Child Interaction Therapy (PCIT) with a 3 year-old boy who consistently opposed and showed disruptive behavior. Following 10 sessions of PCIT over 2 months, F showed significant decreases in his externalizing behavior problems at the end of the treatment. He managed to show less disruptive behavior and improving compliance to the mother. On the other hand, mother’s skills were increased in providing positive attention to the children, giving effective commands, and giving the proper consequences as children respond with compliance or non-compliance. The current case study highlights some advantages and challenges associated with the use of PCIT to treat externalizing behavior problems in very young children in Indonesia.